Robust electronic brake force distribution in hybrid electric vehicles [electronic resource] - Yeoh, Wei Cherng, 1989-, author (2015)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2015